2,2-Dicyanovinyl as a Nonaromatic Aryl Bioisostere: Synthesis, Binding Experiments and SAR Studies of Highly Selective Dopamine D4 Receptor Ligands - Hübner, Harald; Gmeiner, Peter; et al. (Bioorganic & Medicinal Chemistry Letters, 1999)
The phenylpiperazinylmethyl substituted pyrrolylmethylenemalononitriles of type 3 and 4 were synthesized and evaluated as strong and selective dopamine D4 receptor ligands.
UnivIS-Import:2015-03-05:Pub.1999.nat.dchph.lphch.22dicy